The Role of Service Excellence in Improving Service Quality in A Government Agency: A Case Study of Sub-District Office in Bogor - Yusyanah, Yusyanah (Technium Social Sciences Journal, 2022)
Excellent public service is a skill and obligation that must be given by every government apparatus to the community and also to stakeholders. The existence of a paradigm shift in government agencies that is fundamental in various fields of human life is a challenge for public administration, in line with the increasing need for efficient and responsive public services where the government becomes the focus of the community on administrative matters that are obligatory as civil servants so that services to the community are expected to be provided in a timely manner. However, until now, there are still many complaints from the community regarding the poor service provided by officials in the government agencies. This research is intended to answer the questions what aspects of services are complained about by the public and how efforts are being made so that service excellence can be applied in a government agency. This is a qualitative research with a case study approach. Data collection was carried out by semi-structured interviews with 6 community representatives with the aim of finding out whether the staff in the agency had carried out their duties to serve the community in accordance with policies and regulations in excellent service. In this study, the researcher also interviewed 2 staff with the aim of knowing whether excellent service is a priority in serving the community. This study proves that there are important aspects that must be improved in the public service, namely human resources and tangibles.